Serological characteristics and immunohematological difficulties in autoimmune hemolytic anemia patients: A retrospective analytical study from South India - Dibyajyoti Sahoo; S. Anuragaa (Asian Journal of Transfusion Science)
INTRODUCTION: Autoimmune hemolytic anemia (AIHA) is a condition in which there is decreased survival of red blood cells (RBC) due to the destruction of RBC by autoantibodies. AIHA is classified into warm, cold, and mixed according to temperature sensitivity. The antibodies may be immunoglobulin G, immunoglobulin M, immunoglobulin A, or complement proteins, and hemolysis may be intravascular or extravascular. The present study was done to find out serological characteristics of AIHA patients in our population. MATERIALS AND METHODS: During the study, a total of 112 patients’ samples were analyzed. All immunohematology workup, including blood grouping, direct Coombs test (DCT), indirect Coombs test (ICT), monospecific DCT, and alloantibody identification, were done. RESULTS: A maximum number of patients were in the age group of 16–45 years (69.6%). Primary AIHA (56.25%) is more common than secondary AIHA. Females (73.2%) were more affected than men, mostly due to the prevalence of autoimmune disease more in females. Warm AIHA (58%) was more common, followed by mixed (33%) and cold (9%). Grouping discrepancy was seen in 30 (26.8%) cases. CONCLUSION: Warm AIHA is more common in our population followed by mixed and cold types. Blood group discrepancy seen in good proportion of AIHA patients, therefore meticulous immunohematological work up plays an essential role in these patients.